Feature of heart rate recovery in young athletes after a bicycle load of different intensity - P. Prusov; I. Iusov (National Electronic Information Consortium (NEICON), 2020)
Objective: to determine the dependence of heart rate recovery indexes from intensity of previous load in young athletes. Materials and methods: the study included 24 young athletes of 13-18 years old. Dynamics of heart rate during 3 minutes of recovery period was studied depending on the intensity of the preceding 4 minutes of bicycle intermittent load to failure. Load power and oxygen consumption were expressed in relative values (rPWCmx and rPomx) taking into account maximum achieved values. Following parameters were determined: 1. Values of pulse decrease in comparison with the end of the load after 0.5, 1 and 3 min; 2. Reaching time for 50% of recovery (t50%HRR); 3. Relation between indexes of heart rate and heart rate of loads end after 0.5, 1 and 3 min (rHR0.5, 1, 3). Results: with increasing of load intensity the heart rate recovery indexes changed differently. The most informative methods for evaluation of load intensity were rHR3/0.5, t50%HRR and heart rate reduction indexes after 0.5 and 1 min calculated on the potential possibility of heart rate recovery. Conclusions: the heart rate recovery indexes reflect the physical exertion of the organism from the maximum level. Multivariate equations to predict load intensity and aerobic capacity are developed.